+0  
 
0
56
2
avatar

\({ \sqrt{5x^2+11}} = x + 5\)

Guest Oct 23, 2018
 #1
avatar+20105 
+2

How would I solve this equation algebraically?
\(\large{ \sqrt{5x^2+11}} = x + 5\)

 

\(\begin{array}{|rcll|} \hline \sqrt{5x^2+11} &=& x + 5 \quad & | \quad \text{square both sides} \\ 5x^2+11 &=& (x + 5)^2 \\ 5x^2+11 &=& x^2+10x+25 \\ 4x^2-10x-14 &=& 0 \quad & | \quad : 2 \\ 2x^2-5x-7 &=& 0 \\ \\ x &=& \dfrac{ 5\pm\sqrt{25-4\cdot 2 \cdot (-7) } } {2\cdot 2 } \\\\ x &=& \dfrac{ 5\pm\sqrt{25+56 } } { 4 } \\\\ x &=& \dfrac{ 5\pm\sqrt{81} } { 4 } \\\\ x &=& \dfrac{ 5\pm 9 } { 4 } \\\\ x_1 &=& \dfrac{ 5 + 9 } { 4 } \\\\ x_1 &=& \dfrac{ 14 } { 4 } \\\\ \mathbf{ x_1 } &\mathbf{ =}& \mathbf{ \dfrac{ 7 } { 2 }} \\\\ x_2 &=& \dfrac{ 5 - 9 } { 4 } \\\\ x_2 &=& -\dfrac{ 4 } { 4 } \\\\ \mathbf{ x_2} &\mathbf{ =}& \mathbf{ -1} \\ \hline \end{array}\)

 

laugh

heureka  Oct 23, 2018
 #2
avatar+372 
+7

\({ \sqrt{5x^2+11}} = x + 5\)... you have this equation.

 

Sqaure both sides to give you \(5x^2 + 11 = (x+5)^2\)

 

Solving this, we get \(5x^2 + 11 = x^2 + 10x + 25\).

 

This is equal to \(4x^2 - 10x - 14 = 0\)

 

Factorizing this equation, we get \((2x-7)(2x+2) = 0\). (You can test that out to see if it matches the previous equation of \(4x^2 - 10x - 14 = 0\).) 

 

Since \((2x-7)(2x+2)\) has to equal zero, at least one of the brackets need to equal zero for the equation to equal zero. Therefore, we can end up with two solutions.

 

\(x\) is either \(\boxed{\frac{7}{2}}\), or \(x\) is \(\boxed{-1}\).

 

cool

KnockOut  Oct 23, 2018

17 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.